Does Tranexamic Acid Reduce the Blood Loss in Various Surgeries? An Umbrella Review of State-of-the-Art Meta-Analysis - Hong, Pan; Liu, Ruikang; Rai, Saroj; Liu, JiaJia; Ding, Yuhong; Li, Jin (Frontiers in Pharmacology, 2022)
Background: Tranexamic acid (TXA) has been applied in various types of surgery for hemostasis purposes. The efficacy and safety of TXA are still controversial in different surgeries. Guidelines in clinical applications of TXA are needed. Materials and method: We systematically searched multiple medical databases for meta-analyses examining the efficacy and safety of TXA. Types of surgery included joint replacement surgery, other orthopedic surgery, cardiac surgery, cerebral surgery, etc. Outcomes were blood loss, blood transfusion, adverse events, re-operation rate, operative time and length of hospital stay, hemoglobin (Hb) level, and coagulation function. Assessing the methodological quality of systematic reviews 2 (AMSTAR 2) and Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) were used for quality assessment of included meta-analyses. Overlapping reviews were evaluated by calculating the corrected covered area (CCA). Result: In all, we identified 47 meta-analyses of which 44 of them were of ‘High’ quality. 319 outcomes were evaluated, in which 58 outcomes were assessed as ‘High’ quality. TXA demonstrates significant hemostatic effects in various surgeries, with lower rates of blood transfusion and re-operation, shorter operative time and length of stay, and higher Hb level. Besides, TXA does not increase the risk of death and vascular adverse events, but it is a risk factor for the seizure (the neurological event) in cardiac surgery. Conclusion: Our study demonstrates TXA has a general hemostatic effect with very few adverse events, which indicates TXA is the recommended medication to prevent excessive bleeding and reduce blood transfusion rate. We also concluded the recommended different dosages of TXA for different types of adult surgery. But we could not draw a unified dosage for different surgeries due to the heterogeneity of experimental design. Systematic review registration： PROSPERO CRD42021240303